ESG reporting in Singapore - Sim, Chai Ying (2013)
At present, there is a global proliferation of demand by various stakeholders for sustainability reporting. In spite of this, reports have demonstrated that predominantly, organizations are bereft in their efforts. Studies have indicated that enterprises in Singapore yields disconcerting statistics in the area compared to their ASEAN counterparts.